2015
DOI: 10.1111/bjh.13494
|View full text |Cite
|
Sign up to set email alerts
|

How we treat delayed haemolytic transfusion reactions in patients with sickle cell disease

Abstract: SummaryTransfusion therapy is effective in the prevention and treatment of many complications of sickle cell disease (SCD). However, its benefits must be balanced against its risks, including delayed haemolytic transfusion reactions (DHTR). Not only is the relative rate of alloimmunization higher in patients with SCD than in other patient populations, but attendant risks associated with DHTR are even greater in SCD. Clinicians' awareness of DHTR events is poor because symptoms of DHTR mimic acute vaso-occlusiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 74 publications
2
65
0
Order By: Relevance
“…However, the extremely low haemoglobin levels, lower than the pretransfusion levels, indicated that extensive haemolysis including both donor and recipient cells had occurred. This subset of DHTR has been described by some as hyperhaemolytic transfusion reaction and ‘hyperhaemolysis’ syndrome 11. Furthermore, while reticulocytosis is normally a hallmark of haemolytic reactions, reticulocytopenia, as seen in this case, has been a well-documented manifestation of hyperhaemolysis 12 13…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…However, the extremely low haemoglobin levels, lower than the pretransfusion levels, indicated that extensive haemolysis including both donor and recipient cells had occurred. This subset of DHTR has been described by some as hyperhaemolytic transfusion reaction and ‘hyperhaemolysis’ syndrome 11. Furthermore, while reticulocytosis is normally a hallmark of haemolytic reactions, reticulocytopenia, as seen in this case, has been a well-documented manifestation of hyperhaemolysis 12 13…”
Section: Discussionmentioning
confidence: 79%
“…The exact mechanisms responsible for this extensive haemolysis have not been entirely elucidated. One potential reason for the autologous RBC destruction in these patients is the formation of a non-specific antibody that binds complement and destroys both donor and recipient red cells, known as bystander haemolysis 11. Another possible explanation is a hyperactive phagocytic activity of macrophages where a sudden high titre of antibodies leads to destruction of donor cells leading to cytokine release and reactive oxygen radicals that may damage autologous cells 13.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the prediction and prevention of DHTRs in patients with SCD remains a significant clinical challenge, efforts to develop immunosuppressive therapy–based approaches to prevent and/or treat ongoing DHTRs has become a primary focus in the management of transfusion complications in patients with SCD. Several approaches directed at potentially preventing or reducing the consequences of alloantibody‐mediated RBC removal in the setting of an active DHTR or when a DHTR appears likely include steroid‐induced immune suppression and IVIG . In some reported cases, patients have demonstrated an improvement following treatment with either IVIG alone or in combination with corticosteroids; however, some patients required further immunosuppression before recovery .…”
Section: Discussionmentioning
confidence: 99%
“…Another population of patients benefiting from frequent transfusion episodes, sickle-cell disease patients, led to an important discovery: first, they manifest complex hemolytic reactions that involve activated complement and present as essentially inflammatory (25) and second, they are subjected to the most frequent rate of alloimmunization among tracked cohorts of transfused patients (26). This prompted specialists to also examine the inflammatory potential of stored erythrocytes.…”
Section: Transfusion and Inflammation: From Bedside To Benchmentioning
confidence: 99%